PENERAPAN TEKNIK VISUAL STORYTELLING DALAM PROSES PENULISAN NASKAH VIDEO COMPANY PROFILE SEKRETARIAT DAERAH KOTA BOGOR - Videlya Kayla; Alfi Rahmawati; Diadji Kuntoro (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The company profile video project of the Regional Secretariat of Bogor City was carried out as a medium for delivering institutional information to the public through audiovisual media. The company profile video was used to present the institutional profile in a clear and structured manner. This project aims to explain the scriptwriting process, the application of visual storytelling techniques, and the effectiveness of the company profile video through Instagram Reels. The method used was a practice-based approach through pre-production, production, and post-production stages focusing on scriptwriting. The scriptwriting process included research, brainstorming, writing, and revision while considering the suitability between narration and visuals. The application of visual storytelling techniques used Caputo’s theory (2003), including clarity, realism, dynamism, continuity, and intuity. The effectiveness of the video was analyzed descriptively through partner assessment and Instagram insights from @setda_kotabogor.